Acceptance and sustainability of contract farming among youth in Malaysia - Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril; Uli, Jegak; Abu Samah, Bahaman (Science Publications, 2010)
Problem statement: Contract farming is one of the agriculture branches that is ready to be discovered for its huge potential and it is perceived as a new dimension which offers agricultural sustainability. But do the youth as the pillar of this sector do accept agriculture? Thus, this study would like to discover factors that affect acceptance of youth towards contract farming in Malaysia. Approach: This is a quantitative study using a survey form. Data was gathered from 400 undergraduates studying in various tertiary institutions and were analyzed using the PASW software. The data collection process took two months to be completed. Results: Results depict that the respondents studied have a high and positive acceptance towards contract farming. Based on the analysis performed, factors of attitude, knowledge and belief are significant predictors of acceptance towards contract farming. Conclusion/Recommendations: It is believed that the findings of this study would add new perspective on understanding the complexities associated with agricultural sustainability among youth. Results gained provide a sign for policy makers to utilize education as a tool to increase youths.